The Comparison of the Initial TIMI Flow Grade in Acute ST-Elevation Myocardial Infarction Patients Receiving Ticagrelor vs. Clopidogrel before Undergoing Primary Percutaneous Coronary Intervention: A Prospective Cohort Study - Amin Elahifar; Ali Rafati; Mohammad Javad Alemzadeh-Ansari; Yeganeh Pasebani; Behshad Naghshtabrizi; Younes Mohammadi; Seyed Kianoosh Hosseini (Cardiology Research and Practice)
Objective. Primary percutaneous coronary intervention (PCI) is the best treatment for acute ST-elevation myocardial infarction (STEMI). Evidence is in favor of ticagrelor over clopidegrel in STEMI patients regarding the reduction of stent thrombosis risk during and after PCI. We compared initial thrombolysis in myocardial infarction (TIMI) flow in STEMI patients on ticagrelor vs. clopidogrel. Methods. This prospective cohort recruited 160 patients with acute STEMI, referred to the emergency department of Farshchian Heart Center, during March 2018–2019. Before angiography, the patients received clopidogrel (600 mg) or ticagrelor (180 mg) on top of aspirin. Initial TIMI flow was compared between the two groups as the primary outcome. A logistic regression was performed to calculate the predictors of initial TIMI flow. Analyses were performed using R, version 4.2.1. Results. In ticagrelor and clopidogrel groups, the mean ± standard deviation age of the patients was 59.46 ± 13.11 and 61.34 ± 11.08 years (p value = 0.33), respectively. In the ticagrelor and clopidogrel groups, initial TIMI flow grades were as follows: 0 : 50% and 71.2%, I: 26.2% and 16.2%, II: 12.5% and 10%, and III: 12.9% and 2.5%, respectively (p value = 0.005). Final TIMI flow grades were as follows: I: 26.2% and 16.2%, II: 7.5% and 13.8%, and III: 66.3% and 70%, respectively (p value = 0.41). Ticagrelor was associated with significantly higher initial TIMI flow grade compared to the clopidogrel group (adjusted odds ratio: 2.90 (95% CI: 1.51–5.72)). Conclusion. In STEMI patients who were candidates for primary PCI, ticagrelor administration led to a better initial TIMI flow grade compared to clopidogrel.